Carrier free immobilization and characterization of trypsin. (April 2015) - Menfaatli, Esra; Zihnioglu, Figen
Abstract: Pancreatic trypsin was immobilized by cross-linked enzyme aggregates (CLEA) which is a carrier free immobilization method. Ammonium sulfate was chosen for enzyme precipitation which was followed by cross linking of formed aggregates via glutaraldehyde. Concentrations of precipitant and cross linker were respectively optimized as 60% ammonium sulfate and 1% glutaraldehyde. Optimum pH and temperature for CLEA was increased compared to free enzyme. Furthermore, pH, thermal and storage stability were improved. Presence of additives had no effects on enzyme activity. Prepared cross-linked trypsin aggregates are convenient for in situ protein fragmentation and can be used for protein identification.